Are cesarean section rates higher in uncomplicated pregnancies with midwife directed care and in alternative birth settings?. Issue 11 (November 2015) - Hoyt, John; Daly, Sarah
Abstract : Evidence‐Based Answer : For patients who receive intrapartum care by midwives in hospital settings, the cesarean section rate is not statistically different from that for women of similar risk who receive traditional inpatient intrapartum care (SOR: A, systematic review). Alternative birthing environments within a hospital setting have the same cesarean section rates as standard hospital obstetric wards (SOR: A, systematic review).